1984
DOI: 10.1007/bf01213221
|View full text |Cite
|
Sign up to set email alerts
|

Clastogenic effects in human lymphocytes of power frequency electric fields: In vivo and in vitro studies

Abstract: In vivo and in vitro studies of the clastogenic effects of power frequency electric fields and transient electric currents have been performed. For the in vivo investigation peripheral lymphocytes from twenty switchyard workers were screened for chromosome anomalies. The rates of chromatid and chromosome breaks were found to be significantly increased compared to the rates in 17 controls. Exposure of human peripheral lymphocytes, in vitro, to a 50-Hz current with 1 mA/cm2 current density did not induce any chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 17 publications
1
30
0
1
Order By: Relevance
“…Of eight cytogenetic studies of workers exposed to EMF [Bauchinger et al, 1981;Nordenson et al, 1984Nordenson et al, , 1988Nordenson et al, , 1997Valjus et al, 1993;Skyberg et al, 1993;Elias et al, 1989;Jelmert et al, 1994], seven found increased levels of chromosomal aberrations; only Bauchinger et al [1981] found no difference between exposed and controls. Nordenson et al [1997] studied chromosomal aberrations in electrified railway engine drivers and reported a fourfold increase compared with controls.…”
Section: Occupational Exposuresmentioning
confidence: 95%
“…Of eight cytogenetic studies of workers exposed to EMF [Bauchinger et al, 1981;Nordenson et al, 1984Nordenson et al, , 1988Nordenson et al, , 1997Valjus et al, 1993;Skyberg et al, 1993;Elias et al, 1989;Jelmert et al, 1994], seven found increased levels of chromosomal aberrations; only Bauchinger et al [1981] found no difference between exposed and controls. Nordenson et al [1997] studied chromosomal aberrations in electrified railway engine drivers and reported a fourfold increase compared with controls.…”
Section: Occupational Exposuresmentioning
confidence: 95%
“…Some studies have been performed on samples taken from individuals professionally exposed. Increases in micronuclei frequencies and chromosomal aberrations have been observed in lymphocytes of photocopying machine workers (Iravathy Goud et al 2004), powerline operators and railwaymen (Nordenson et al 1984, 2001, Skyberg et al 1993, Valjus et al 1993.…”
Section: Introductionmentioning
confidence: 99%
“…In a S wedish study of 20 high-vo ltage substatio n m aintenan ce work ers, ind ications of work-rel ated reproductive hazards we re found (14 ). This result was followed up in tw o studies of po wer substat ion worke rs ex pos ed to electro magnetic fields with transie nt currents (10,15). Th e resul ts fro m bo th studies were pooled , and an incr eased number of chro moso m e aberration s wa s found.…”
Section: Discussionmentioning
confidence: 67%
“…As for alcohol con sumption, use of prescribed medicine, infections durin g the last three month s, off-work chemica l expo sure, chroni c diseases, and diagnostic radiography, there were only minor differences between the exposed subjects and the matched referents. The mean expo sure time in cable testing was I I (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] years; the test splicers had a mean emplo yment time of 12 years, and the corresponding value for the engineers was 9 years. Blood samples were collected by venipuncture.…”
Section: Methodsmentioning
confidence: 99%